Bithiazole: An Intriguing Electron‐Deficient Building for Plastic Electronic Applications. Issue 10 (2nd March 2017) - Su, Haw‐Lih; Sredojevic, Dusan N.; Bronstein, Hugo; Marks, Tobin J.; Schroeder, Bob C.; Al‐Hashimi, Mohammed
Abstract : Heterocyclic thiazole units can be incorporated into organic semiconducting materials, thus allowing the optoelectronic properties of a material to be tuned without significantly perturbing its molecular structure and affording high‐performance acceptor polymers for use in bulk‐heterojunction solar cells and as organic field‐effect transistors. Abstract : The heterocyclic thiazole unit has been extensively used as electron‐deficient building block in π‐conjugated materials over the last decade. Its incorporation into organic semiconducting materials is particularly interesting due to its structural resemblance to the more commonly used thiophene building block, thus allowing the optoelectronic properties of a material to be tuned without significantly perturbing its molecular structure. Here, we discuss the structural differences between thiazole‐ and thiophene‐based organic semiconductors, and the effects on the physical properties of the materials. An overview of thiazole‐based polymers is provided, which have emerged over the past decade for organic electronic applications and it is discussed how the incorporation of thiazole has affected the device performance of organic solar cells and organic field‐effect transistors. Finally, in conclusion, an outlook is presented on how thiazole‐based polymers can be incorporated into all‐electron deficient polymers in order to obtain high‐performance acceptor polymers for use in bulk‐heterojunction solar cells and as organic field‐effect transistors. Computational methods are used to discuss some newly designed acceptor building blocks that have the potential to be polymerized with a fused bithiazole moiety, hence propelling the advancement of air‐stable n‐type organic semiconductors.